Pengaruh Perubahan Dimensi Dan Jenis Material Terhadap Umur Worm Screw Press Type AP-17 Pada PTPN V Sei. Garo - Apri Setiawan; Syafri Syafri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
PTPN V Sei. Garo uses the recommended worm screw for about 1000 hours of work, but because of the often unexpected things sometimes the age of worm screw is always lower. To anticipate these problems then modified the material and dimensions are required. The purpose of this study is to determine the effect of material changes and dimensions on the age of worm screw. Then do a simulation using Autodesk Inventor to know the maximum and maximum deflection. After the calculation manually, based on data worm screw type AP-17 screw life worms obtained about 777 hours of work (± 1 month). The modifications were made for the addition of age: modified thick screw and pitch distance was obtained age of 1388 working hours and 920 hours of work, after the simulation using Autodesk Inventor was obtained maximum voltage 3.1 of Mpa and 6.3 Mpa with maximum deflection of 0.01 mm. However, by increasing the thickness and spacing of the screw pitch resulted in reduced screw press capacity, consequently impacting the capacity of the plant. There were many disadvantages from the modification of the dimensions, therefore the modification of matrial from AISI 1020 to AISI 1080 was obtained the screw worm life age of about 2190 hours of work, after simulation using Autodesk Inventor was obtained maximum voltage of 6.4 MPa with maximum deflection worth of 0. 01 mm.Key words: Screw Worm Age, Modified Dimension, Modified Matrial, Autodesk Inventor Simulation